Intra-raw material variability and use-wear accrual: A continuing exploration - Lerner, Harry Joseph (Journal of Lithic Studies, 2014)
This paper presents the latest results of an ongoing research initiative into the role of lithic raw material variability in use-wear formation. The present study continues recent exploration of wear formation associated with working dry hide. The work presented here expands on a recently published study of two raw materials from the American Southwest [San Juan Fossiliferous Chert (SJF) and Yellow Silicified Wood (YSW)] (Lerner, In Press) by presenting the analysis of two additional materials [Morrison Undifferentiated Gray Chert (MUG) and Brushy Basin Silicified Siltstone (BB)] using the same quantitative measures from the previous study (area percent, density, average intensity.) The methods used have broad geographic and temporal applicability, thus the potential for contributing to greater standardization in the quantification of archaeological use-wear.